Ekonomi Ungu: Eksistensi Ekonomi Berbasis Budaya Studi Kasus Dodol Betawi - Rizky, Putri; Sitorus, Onny Fitriana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aimed to describe how purple economy can reflect cultural values on goods and services in the Betawi dodol business. The object of this research is Mr. Marno's dodol Betawi. For this sampling technique using purposive sampling with the subject of processors, service employees, and consumers. This research uses descriptive qualitative methods with data collection using observation, interviews, and documentation. The analysis technique used is interactive model analysis. Data validity uses source triangulation, technique and theory triangulation. The findings in the field are dodol which has been attached to Betawi culture so that when at certain events dodol is the most sought after by having various flavors and variants of Betawi special cakes and in the services provided with hospitality so that anyone who comes will feel comfortable. The limitation in this study is that it tends to be subjective to dodol betawi culinary MSMEs only because it cannot be applied to other types of fields, so this research has limited sources and phenomena in MSME. In Indonesian literature, the purple economy has not been widely or minimally discussed in national literature but with a small scope and to start with it is very possible in MSME, especially Betawi dodol MSME because they are attached to their culture and economy.